Pitx2 in Embryonic and Adult Myogenesis - Hernandez-Torres, Francisco; Rodríguez-Outeiriño, Lara; Franco, Diego; Aranega, Amelia E. (Frontiers in Cell and Developmental Biology, 2017)
Skeletal muscle is a heterogeneous tissue that represents between 30-38% of the human body mass and has important functions in the organism, such as maintaining posture, locomotor impulse or pulmonary ventilation. The genesis of skeletal muscle during embryonic development is a process controlled by an elaborate regulatory network combining the interplay of extrinsic and intrinsic regulatory mechanisms that transform myogenic precursor cells into functional muscle fibres through a finely tuned differentiation program. However, the capacity of generating muscle still remains once these fibres have matured. Adult myogenesis resembles many of the embryonic morphogenetic episodes and depends on the activation of satellite cells that have the potential to differentiate into new muscle fibres. Pitx2 is a member of the bicoid family of homeodomain transcription factors that play an important role in morphogenesis. In the last decade, Pitx2 has emerged as a key element involved in the fine-tuning mechanism that regulates skeletal-muscle development as well as the differentiation and cell fate of satellite cells in adult muscle. Here we present an integrative view of all aspects of embryonic and adult myogenesis in which Pitx2 is involved, from embryonic development to satellite-cell proliferation, fate specification, and differentiation. Those new Pitx2 functions on satellite-cell biology might open new perspectives to develop therapeutic strategies for muscular disorders